UiPath certified advanced RPA developer (UiARD). (Pearson IT Certification, 2023)
Sneak Peek The Sneak Peek program provides early access to Pearson video products and is exclusively available to Safari subscribers. Content for titles in this program is made available throughout the development cycle, so products may not be complete, edited, or finalized, including video post-production editing. 5 Hours of Video Instruction Overview: This video course is your complete guide to self-study for passing the UiPath Advanced RPA Developer course. Lead the future of work by becoming a UiPath Certified Professional. Gain in-demand skill for the roles of Advanced RPA Developer, Solution Architect, RPA Architect, and more. About the Instructor Leon Petrou is a UiPath MVP, Industrial Engineer (BEng, Cum Laude) and founder of RPA consultancy, FutureRPA.com. Leon is also the lead instructor at the CompleteRPABootcamp.com, where he has helped thousands of students learn UiPath, get certified and land high-paying jobs as RPA Developers. To date, Leon has taught over 50,000 students worldwide, both in-person and online. Leon prides himself on helping his students take the next step in growing their careers by making learning fun and easy. Be sure to visit the Complete RPA Bootcamp website. Skill Level: Intermediate - Advanced What You Will Learn: Prepare to pass the UiPath Certified RPA Associate exam Advance your skills as an RPA developer and prepare for the UiPath Advanced RPA Developer (UiARD) Exam Master the Robotic Enterprise (RE) Framework for building robust and large-scale automations Design and develop complex, production-level RPA solutions Develop end-to-end RPA projects Build and lead production-level automations using the Robotic Enterprise (RE) Framework Who Should Take This Course: RPA Developers Roles requiring RPA Developer expertise such as RPA Architects, Solution Designers, RPA Engineers, Solution Architects, Process Automation Architects Course Requirements: Preferably completed formal or informal UiPath training wi+th hands-on experience. About The Pearson UiPath Series: UiPath, a global leader in robotic process automation (RPA), provides solutions for businesses to automate routine tasks. The Pearson UiPath Series addresses the needs of today's knowledge workers including RPA Developers, Designers, Solutions Architects who aim to pass the UiPath certifications to further their careers. Whether you're starting out in the RPA field or have been working and want to grow your skill set, Pearson delivers innovative learning products to help you pass your certifications and achieve the learning outcomes you desire. Video includes free access to the academic version of the software platform. Instructions for access provided in Lesson 1. About Pearson Video Training: Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.